NOTES ABOUT ARCHAIC VOCABULARY IN NORTHERN LAMENTATIONS BY E. V. BARSOV - Олеся Дмитриевна Сурикова (Olesya D. Surikova) (Вестник Пермского университета. Российская и зарубежная филология, 2018)
The vocabulary represented in Northern Lamentations collected by E. V. Barsov is still poorly examined and studied by linguists and folklorists, which is a very important problem, yet unsolved. Many words in this collection cannot be found in dialect dictionaries, which means that they are not seen by dialectologists, etymologists and ethnolinguists, though their structure, semantics, etymology and geography could be of interest for researchers. These words can be considered archaic, as they disappeared from speech at least in the second half of the 19th century, and give the possibility to see rituals and rites that are “behind” them. This vocabulary implements archaic semantic models, embodies ancient metaphors and peculiarities of the archaic way of thinking and, of course, needs interpretation. The article consists of two sketches, in which the author considers some words from Barsov’s lamentations. The first sketch refers to semantic dialecticisms – derivatives from the verb pakhat’ : gorepashnitsa , ‘self-denomination of a widow / orphan’, popakhat’ , ‘to sweep the grave on the Trinity Sunday’, spakhat’sya, ‘to show interest, attention, to care’. It has been established that the word gorepashnitsa is a derivative of the word pakhat’ (to plough) and functions in the frames of the Russian North archaic semantic transition model ‘to work hard’ → ‘to suffer’. The words popakhat’ and spakhat’sya originate from the word pakhat’ in a more ancient general Slavic meaning ‘to sweep’. The second sketch analyzes the context meaning of the verb otlit’, , which we meet in one of the lamentations as a part of a prayer: “O Lord, save thy bad people, pour off, o Lord, to these evil people, Meet them, o Lord, on the Second Advent”. One of the versions says that this verb in this context embodies the notion of the feud (to be more precise – of the mutual spill of the “valuable” liquids); another version refers to magical rites with the spillage of water and / or wax.